Apache ZooKeeper essentials : a fast-paced guide to using Apache ZooKeeper to coordinate services in distributed systems /: a fast-paced guide to using Apache ZooKeeper to coordinate services in distributed systems. (2015) - Haloi, Saurav
No abstract available